The Financial Determinants of Audit Report Lag with Auditor Specialization as a Moderating Variable in Manufacturing Firms - Rahman Sastrawan; Andika Patria; Siti Lestari (Jurnal Akuntansi dan Keuangan, 2026)
This research seeks to assess the effect of financial indicators on indicators of financial distress, operational complexity, liquidity, leverage, and profitability on the delay in reporting audit, with auditor expertise acting as a moderating factor in manufacturing firms registered on IDX within the food and beverage sector from 2021 to 2024. The observation comprised 47 objects, including 26 companies purposively selected. The data analysis employed the WarpPLS application with a Partial Least Squares (PLS)- based Structural Equation Modelling (SEM) model. The results reveal that operational complexity, liquidity, and leverage do not affect audit report latency; however, financial distress and profitability exert a considerable detrimental effect, consequently reducing audit report lag. An auditor’s specialty can’t enhance or diminish the impact of financial distress, operational complexity, liquidity, leverage, and profitability on audit report latency, but it can extend audit report lag